Changes in teaching Graduate Skills, including ethics, since 2010: Professional Communication Studies, University of Cape Town - Gwynne-Evans, Alison; English, Jane (South African Journal of Higher Education, 2016)
Professional Communication Studies (PCS) is situated within the Faculty of Engineering in the University of Cape Town. PCS runs courses that supplement the hard engineering courses with skills aimed at equipping students for their professional career as regards report, business proposal and thesis writing and presentation skills. UCT policy has focussed on ‘graduateness’ for students as they prepare for the challenges of professional life. Ethics is a key area of graduateness. The professional body responsible for maintaining standards for the engineering professions, the Engineering Council of South Africa (ECSA), has initiated requirements prioritising ethics. PCS seeks to respond to changes in the assessment requirements of ECSA and to the challenges of UCTs focus on ‘graduateness’. Innovations in the teaching of ethics within PCS in 2011/2012 are explored. The paper concludes by summarising how changes in policy require creative engagement by the department in order to have positive and lasting impact. Keywords Professions, Communication, Graduate skills, Ethics